2022
DOI: 10.1056/nejmoa2109449
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Three Rounds of Mass Azithromycin Administration for Yaws Eradication

Abstract: Background Treponema pallidum subsp. pertenue causes yaws. Strategies to better control and hopefully eliminate yaws are needed. Methods We conducted an open-label cluster-randomized community trial in a yaws-endemic area of Papua New Guinea. Thirty-eight wards were randomized to receive either one mass drug administration (MDA) round followed by two target treatment of active cases rounds (control arm) or three MDA rounds (expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The differences observed between the studies may be due to the different specimen collection periods or other technical differences. There was a large difference in sequencing depth between the studies, with this study having approximately 17x more depth than the previous study (11,418 median microorganism reads vs 678 median reads with species level identification in the CU specimens, respectively). Choice of annotation methods between the previous study (MEGAN and Kraken) and our study (MetaPhlAn3) may also explain some differences found in these two studies.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 61%
See 2 more Smart Citations
“…The differences observed between the studies may be due to the different specimen collection periods or other technical differences. There was a large difference in sequencing depth between the studies, with this study having approximately 17x more depth than the previous study (11,418 median microorganism reads vs 678 median reads with species level identification in the CU specimens, respectively). Choice of annotation methods between the previous study (MEGAN and Kraken) and our study (MetaPhlAn3) may also explain some differences found in these two studies.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 61%
“…Since the overall prevalence of CU was still at 0.8% after 42 months, the trial was halted due to the failure to achieve the primary endpoint, eradication of yaws [ 10 ]. Another yaws eradication community-based trial in the Namatanai District of the New Ireland Province of Papua New Guinea used three rounds of MDA of azithromycin given every six months; however, this trial also failed to eradicate yaws [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of co-endemicity of skin-NTDs have undergone several investigations with treatment which have certainly reduced the incidence of yaws (10). The results of this study suggest that additional efforts are needed to control yaws in the three countries where the disease is endemic, in particular the number of rounds of MDA which can be reviewed to significantly reduce the incidence of the disease (51). More than 80% of yaws like ulcers were not yaws (542/3085), suggesting that proper identification and management of other cutaneous ulcers, such as H. ducreyi , is important to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…A major concern has been the identification of a small number of cases of yaws which have developed resistance to azithromycin [5]. In Papua New Guinea, long term follow up studies have reported Azithromycin resistant yaws cases 24 months post MDA [6,7]. Two point mutations (A2059G and A2058G in the 23S ribosomal genes) are known to confer resistance to azithromycin in T.pallidum subsp pallidum, and both have now has been detected in T.pallidum subsp pertenue.…”
Section: Introductionmentioning
confidence: 99%